Effectiveness Of Onion Compress On The Event Swelling In Children After Pentabio Immunization At Puskesmas Plawad In 2023 - Lilis Novitasari; Mariyani Mariyani (International Journal of Health and Pharmaceutical (IJHP), 2024)
Background : Immunization is an effort to actively generate/increase a person's immunity against a disease so that if one day they are exposed to the disease they will not get sick or only experience a mild illness. Swollen immunization marks are a normal side effect and are experienced by many people. This swelling is the body's reaction to the vaccine administration process and is a sign that the body is starting to form immunity to disease. Research purposes : Knowing the effectiveness of shallot compresses on the incidence of swelling in children after immunization at the Plawad Health Center in 2023. Research methods : This type of research is analytic observational with a case control design. The sample of this study were children who received DPT immunization. The sample technique uses accidental sampling technique. Data collection uses an observation sheet. The data analysis used was univariate analysis and bivariate analysis using the chi square test. Research result : The results of the chi square test with a p value of 0.000 <0.05 indicate that there is an effect of onion compresses on the incidence of swelling after immunization. Thus it can be seen that onion compresses are effective in alleviating the incidence of swelling in children after immunization. Based on the analysis of the Odds Ratio (OR) it was obtained at 8.250 (95% CI = 2.530-26.900). This shows that onion compresses are 8,250 times effective in overcoming swelling after immunization. Conclusion : Onion compresses are effective in overcoming the incidence of swelling in children after immunization.